The Importance Of Magnesium In The Human Body And Rich- Foods In Magnesium - Khayrullayeva Lobar (Global Scientific Publishing, 2023)
In essence, every single cell has to have energy for it to react to a lot of signals that include growing, dividing, initiating or stopping the synthesis of a particular element, triggering an immunity response and beginning programmed death via apoptosis. The signals, communicated, executed and terminated in individual cells and between cells need to be interpreted correctly.
Keywords: magnesium; cell; deficiency